2001
DOI: 10.1095/biolreprod65.3.805
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Reproductive Experience Enhances Early Postnatal Outcome Following Gestation and Birth of Rats in Hypergravity1

Abstract: A major goal of space life sciences research is to broaden scientific knowledge of the influence of gravity on living systems. Recent spaceflight and centrifugation studies demonstrate that reproduction and ontogenesis in mammals are amenable to study under gravitational conditions that deviate considerably from those typically experienced on Earth (1 x g). In the present study, we tested the hypothesis that maternal reproductive experience determines neonatal outcome following gestation and birth under increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 35 publications
2
13
1
Order By: Relevance
“…We and others have previously shown that in pregnant and lactating mammals, exposure to HG has profound eVects on the dam's homeorhetic responses to pregnancy and lactation, evident in changes in rates of lipogenesis in mammary, liver and adipose tissue which likely result in impaired milk fat production and reduced milk bands in pups resulting in decreased neonatal survival (Lintault et al 2007;Megory and Oyama 1984;Ronca et al 2001). Oyama (1984, 1985) were the Wrst to postulate that aberrant PRL secretion impairs lactogenesis and subsequent neonatal survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have previously shown that in pregnant and lactating mammals, exposure to HG has profound eVects on the dam's homeorhetic responses to pregnancy and lactation, evident in changes in rates of lipogenesis in mammary, liver and adipose tissue which likely result in impaired milk fat production and reduced milk bands in pups resulting in decreased neonatal survival (Lintault et al 2007;Megory and Oyama 1984;Ronca et al 2001). Oyama (1984, 1985) were the Wrst to postulate that aberrant PRL secretion impairs lactogenesis and subsequent neonatal survival.…”
Section: Discussionmentioning
confidence: 99%
“…Oyama (1984, 1985) were the Wrst to postulate that aberrant PRL secretion impairs lactogenesis and subsequent neonatal survival. Our recent series of studies revealed a number of other PRL-associated changes with alterations in g-load ranging from perturbation in mammary, liver and adipose metabolism, mother-infant interactions to neonatal mortality during the peripartum period (Lintault et al 2007;Ronca et al 2001;Zakrzewska et al 2004). Our further studies revealed that the PRLR was downregulated in the key sites for lipogenesis, particularly, the mammary gland (Patel et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…We used only multiparous females to reduce the risks of misbehaving with the pups [19], and the adult mice were centrifuged at a level of 2G for at least 8 weeks before the experiments, to habituate them to the centrifugation and reduce the stress during the experimental phase. The experiments involved four groups of mice centrifuged at 2G during different periods of their development.…”
Section: Animalsmentioning
confidence: 99%
“…We and others showed that survival rates of pups born to rat dams exposed to 1.5- to 2-times Earth's gravity during the latter half of pregnancy were reduced by 5 to 40% (Megory and Oyama, 1984; Baer et al, 2000; Ronca et al, 2001). However, if neonatal pups were removed from the hypergravity environment and cross fostered to non-manipulated dams, mortality did not occur (Baer et al, 2000).…”
Section: Introductionmentioning
confidence: 97%
“…We previously identified gravity as an environmental variable that produces major graded changes in mammary metabolic activity and reduces pup survival (Ronca et al, 2001; Plaut et al, 2003). We and others showed that survival rates of pups born to rat dams exposed to 1.5- to 2-times Earth's gravity during the latter half of pregnancy were reduced by 5 to 40% (Megory and Oyama, 1984; Baer et al, 2000; Ronca et al, 2001).…”
Section: Introductionmentioning
confidence: 99%